Programming with C++ : - Hubbard, John (McGraw Hill, 2000)
Programming with C++, Second Edition, is an update of the highly successful first editiona bestseller in Schaum's computer science lineand reflects the new ISO standard for C++, rendering previous C++ guides obsolete. Essential for programmers, 280,000 computer science students taking first-level classes, and thousands of advanced placement students, this book is the perfect supplement to the leading textbooks in introductory and higher-level programming courses.